Article Commentary: Underutilization of Medications to Treat Opioid Use Disorder: What Role Does Stigma Play?. Issue 4 (October 2019) - Allen, Bennett; Nolan, Michelle L.; Paone, Denise
There is consensus in the scientific literature that the opioid agonist medications methadone and buprenorphine are the most effective treatments for opioid use disorder. Despite increasing opioid overdose deaths in the United States, these medications remain substantially underutilized. For no other medical conditions for which an effective treatment exists is that treatment used so infrequently. In this commentary, we discuss the potential role of stigma in the underutilization of these opioid agonist medications for addiction treatment. We outline stigma toward medications for addiction treatment and suggest that structural and policy barriers to methadone and buprenorphine may contribute to this stigma. We offer pragmatic public health solutions to reduce stigma and expand access to these effective treatments.